Violet Archer, Jean Coulthard, and Barbara Pentland Remembered - Deaville, James; Kenneson, Claude; Bruneau, William; Keillor, Elaine; Munn, Alexandra; Hughes, Neil; Colton, Glenn; Beckwith, John (Canadian University Music Review / Revue de musique des universités canadiennes, 2000)
In a bizarre coincidence, three important Canadian women composers from the same generation recently died within five weeks of each other: Barbara Pentland on 6 February 2000, Violet Archer on 22 February 2000, and Jean Coulthard on 9 March 2000. As a tribute to their lives and work, this colloquy gathers remembrances of them by friends and colleagues, ranging from brief anecdotes to extended memoirs. It is thus a collection of primary documents, which yield many new insights into the lives of our composers, ranging from personal habits to the way they taught composition.